Three proposals for revitalising the European Union - Tonveronachi, Mario (PSL Quarterly Review, 2017)
Widespread perception that convergence on the current set of rules is not capable of producing convergence on results, or anyway generally better results, has increased the socio-political fragmentation inside the European Union. The result has been an increasing demand for a partial re-nationalisation of sovereign powers, whose physiology comes from the necessity of higher national flexibility. Asking how feasible changes in the current set of rules could accommodate the increased demand of national flexibility, the paper focuses on the euro area and proposes to revise the monetary operations of the European Central Bank, current fiscal rules, and the financial regulatory approach. The proposed new design is based on the premise that no changes in the Treaty on the Functioning of the European Union are possible at the moment, even though a minimum political convergence is necessary. If successfully implemented, the proposal would contribute to give a viable perspective to the design of the Economic and Monetary Union, capable of attracting those EU non-euro area countries that consider the mismanagement of the recent crisis and of its after-effects reason enough for resisting further losses of sovereignty. JEL: E52, E62, F33, F36, F45, G28